A Case Series of Median Arcuate Ligament Syndrome With Varied Presentations - Al-hakam; Yousef Adawi; Mohammad Abu-ghosh; Lila H. Abu-hilal MD; Khaled N. Al Shawwa MD; Tawfiq AbuKeshek MD; Mohammed Maree MD (SAGE Publishing, 2023)
Median arcuate ligament syndrome (MALS) is characterized by the constriction of the celiac trunk caused by fibrous connections originating from the median arcuate ligament (MAL) and diaphragmatic crura. It presents with symptoms often leading to misdiagnosis. In this study, we present three cases of MALS, with distinct manifestations. These cases were diagnosed through comprehensive investigations and managed successfully using laparoscopic decompression. The diagnosis of MALS poses challenges due to its variable presentations and overlap with other conditions. Diagnostic imaging techniques such as Doppler ultrasound, computed tomography (CT) scans and angiography play a role in confirming the diagnosis. Laparoscopic decompression has proven to be a treatment option that relieves symptoms and restores blood flow. This series highlights the importance of considering MALS as a cause for abdominal pain cases. Early detection and the use of diagnostic techniques can result in favorable outcomes.